Concept for Curriculum Development for Islamic Religious Education in Madrasas - Djufri, Ayulinda; Yahiji , Kasim; Ondeng, Syarifuddin; Arif, Muh. (Newinera Publisher, 2023)
This study explains the concept of developing the Islamic Religious Education curriculum in madrasah The method used in this study uses a library research method or approach, that literature or literature study can be interpreted as a series of activities related to the method of collecting library data, reading and recording and processing research materials. Curriculum development is important to be fulfilled by the competence and quality possessed by the head of the madrasah as a leader in educational institutions, this is expected to be able to contribute to the development of the Islamic education curriculum, not only conceptual theoretical but can be implemented in the operational context of educational praxis.